2022
DOI: 10.1021/jacs.2c08623
|View full text |Cite
|
Sign up to set email alerts
|

Tröger’s Base Chemistry in Solution and in Zr(IV)-Based Metal–Organic Frameworks

Abstract: Troger's base (TB) and its derivatives have been studied extensively due to their unique concave shape stemming from the endomethylene strap. However, the strap-clipped TB chemistry has been largely overlooked in metal−organic framework (MOF) solids, leading to a gap in our knowledge within this field. In this work, we report the in situ strap elimination of a carboxylate-carrying TB in the presence of formic acid, both in solution and in Zr(IV)-based MOFs. In the solution system, the methanodiazocine nucleus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Therefore, the scattering arising from the disordered solvent and Et 2 NH 2 was eliminated by utilizing the SQUEEZE subroutine of the PLATON software suite. Similarly, the free solvents in the crystal structure of 2 also were removed by the same method. , Thus, the final formulas are inconsistent with those in Table S1 generated after the SQUEEZE process during the structure refinement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the scattering arising from the disordered solvent and Et 2 NH 2 was eliminated by utilizing the SQUEEZE subroutine of the PLATON software suite. Similarly, the free solvents in the crystal structure of 2 also were removed by the same method. , Thus, the final formulas are inconsistent with those in Table S1 generated after the SQUEEZE process during the structure refinement.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the aforementioned considerations, (Et 2 NH 2 )­[Zn 3 (TCPE)­(adenine) 2 CH 3 COO]·DEF·3H 2 O ( 1 ), an anionic framework, was synthesized using Zn 2+ ions, adenine, and H 4 TCPE. By regulating the deprotonation and hydrolysis capacity of the solvent used for synthesis, , another neutral framework was obtained, [Zn 3.5 (adenine)­(TCPE) 1.5 (DMA)­(H 2 O) 0.5 ]·2DMA·2H 2 O ( 2 ) (Scheme ). Besides high stability, both MOFs contain high porosity, adsorption capacity for C 2 H 2 , and excellent C 2 H 2 /CO 2 selective separation performance.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) possess unique porosity, stability, and chemical and physical properties . This class of materials has been widely employed in a myriad of applications including the heterogeneous catalysis. MOFs can be exploited as a solid catalyst in the ODS reactions due to their high density of active sites, various metal centers, adjustable pore shapes and sizes, high surface areas, and permanent porosities. , Furthermore, MOF pores can serve as individual “reactors” given their ability to host other catalytically significant molecules. , Although many MOF materials have been identified and synthesized, only a few studies have been devoted to the application of pristine MOFs as ODS catalysts. , Besides, the ODS catalytic behavior of MOFs could be enhanced through functionalization (especially by amide functional groups) and/or in combination with other catalytically active molecules (e.g., POMs) …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the self-assembly of a metal ion and polycarboxylates with the assistance of an N-donor ligand is a very effective method . However, under specific reaction conditions, organic ligands may undergo unexpected transitions when interacting with metal centers, thus wonderfully tuning the physical properties of the complexes. Such deformations of ligands are of great interest in coordination chemistry.…”
Section: Introductionmentioning
confidence: 99%